Tunneling‐Related Leakage Currents in Coaxial GaAs/InGaP Nanowire Heterojunction Bipolar Transistors. Issue 2 (13th September 2020) - Liborius, Lisa; Bieniek, Jan; Possberg, Alexander; Tegude, Franz-Josef; Prost, Werner; Poloczek, Artur; Weimann, Nils
Abstract : Herein, a detailed analysis of leakage mechanisms in epitaxially grown nanowire heterojunction bipolar transistors (NW‐HBTs) is presented. Coaxial npn‐GaAs/InGaP core–multishell nanowires are grown via gold‐catalyzed metalorganic vapor phase epitaxy, processed to three terminal devices and electrically characterized. The key for successful NW‐HBT device functionality is the identification of tunneling as the dominant leakage mechanism in highly doped nanowire pn‐junctions. The suppression of forward tunneling currents by adjustment of the tunneling barrier width reduces the junction leakage current density into the nA cm −2 regime, which is further verified by tunneling‐related electroluminescence measurements. In addition, the suppressed tunneling accordingly increases the number of electrons that are injected from the n‐emitter into the p‐base. The latter effect influences the performance of pn‐junction based devices and is found to enable bipolar transistor functionality. Measured common emitter Gummel plots of the NW‐HBT exhibit a current gain of up to 9 and the transistor function is additionally verified by current‐controlled output characteristics. Abstract : Herein, the systematic suppression of forward tunneling leakage currents in coaxial GaAs/InGaP nanowire pn‐junctions is identified as key factor for the successful demonstration of an npn nanowire heterojunction bipolar transistor. The tunneling leakage reduction, which is verified by electric and optoelectric measurements, is enabled by elongating the necessary tunneling distance via emitter shell thickness adjustments.